The Influence Of Organizational Culture, Job Insecurity, And Job Satisfaction On Employee Productivity - Qristin Violinda; Rita Meiriyanti; Wulandari, Sinta (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: This research aims to determine the influence of organizational culture, job insecurity, and job satisfaction on employee work productivity at PDAM Tirta Amerta, Blora Regency. Design/Methode/Approach: This type of research is quantitative research that uses statistical analysis. The population in this study was 174 employees and the sample determined in this study was 121 employees with a sampling technique using the Slovin formula. This research uses SPSS software to answer the main facts using a list of questionnaires that respondents have answered. Research Finding: The findings in this research are that organizational culture influences employee work productivity at PDAM Tirta Amerta, job insecurity influences employee work productivity at PDAM Tirta Amerta, and job satisfaction influences employee work productivity at PDAM Tirta Amerta, Blora Regency.